Exclusion in all-pay auctions: an experimental investigation - Fehr, Dietmar; Schmid, Julia (Journal of economics & management strategy, 2018)
Contest designers and managers who wish to maximize the overall revenue of a contest are frequently concerned with a trade-off between contest homogeneity and inclusion of contestants with high valuations. In our experimental study, we find that it is not profitable to exclude the strongest bidder in order to promote greater homogeneity among the remaining bidders, even though the theoretical exclusion principle predicts otherwise. This is because the strongest bidders are willing to give up a substantial portion of their expected rent in order to minimize the chance of losing the contest.